Some Interesting Soil Data on Compactness, Erodibility, and other Morphological Features in Sal Forests, Miscellaneous Forest and Taungya in Dehra Dun - Gupta, Raghunath S. (Indian Forester, 1955)
In this investigation, Brinell's hardness number, erodibility, penetrability and apparent density, etc., at different depths of soil in sal forest, miscellaneous forest and taungya is determined in situ. In the forest areas, hardness of top-soil is greater than sub-soil while it is vice versa in taungya. In the latter, cultivation and exposure leads to hard pan layer at a certain depth which may decrease sub-soil water seepage and reserve and increase erosive tendencies in soil mass.